Pengaruh Repetisi Beban Lalu Lintas Harian Terhadap Nilai Kepadatan Perkerasan AC-WC Pasca Konstruksi - Erlangga, Dwiky; Laila Ramadhan, Puji; Saktiadin, Saktiadin (Universitas Sulawesi Barat, 2025)
The compression process should be carried out carefully in each asphalt coating sheet, in addition to the availability of heavy equipment should be taken into account its productivity. Problems that are often faced by contractors in the field sometimes cause damage to heavy equipment and decrease in productivity, although the material mixture is already in accordance with the quality and the compression process follows the number of tracks planned, but the results of the field compression tests do not meet the specifications as long as the contractor in execution has to increase the amount of compression tracks and working hours of use of heavy equipment on the field. Concrete measures are needed to suppress the reduction in the efficiency of work so as not to affect increased costs and time. The daily additional load factor of traffic can be used as a parameter that helps the compression process, so in achieving the expected quality target does not always depend on the use of heavy equipment. This study analyzed the comparison of the percentage of AC-WC density to the repetition value of the load growth of post-sourcing traffic and the PHO time of the project. The results of the calculation showed that the AC - WC density value in segment 1 was 100.42%, while segment 2 was 99.73%, and segment 3 was 98.82%. Then the PHo time value of project 1 was 104.44% with a load repeat of 43.708,75 cesa, while in segment 2 it was 100.20% with load repeats of 1.277.57 cesa and in segment 3 it is 99.20%, with a charge repeat value of 1.368.75 cesa.